Effective MRD clearance and long-term survival with CD19 CAR-T in pediatric B-ALL patients with MRD positivity or chemotherapy intolerance - Wang, Yu; Jia, Yue-ping; Lu, Ai-dong; Zhang, Le-ping; Xue, Yu-juan; Zeng, Hui-min (Frontiers in Immunology, 2025)
BackgroundWhile CD19-directed chimeric antigen receptor T-cell (CAR-T) therapy demonstrates remarkable efficacy in relapsed/refractory (R/R) ALL, its application in earlier treatment lines requires further investigation. This study aimed to evaluate the efficacy, safety, and cellular kinetics of CD19 CAR-T therapy in pediatric B-cell ALL (B-ALL) patients with minimal residual disease (MRD) positivity or chemotherapy intolerance.MethodsBetween 2017 and 2021, 50 eligible pediatric B-ALL patients (with positive MRD or chemotherapy intolerance) received CD19 CAR-T therapy. Efficacy endpoints included complete remission (CR), MRD-negative CR (MRD-CR), overall survival (OS), and leukemia-free survival (LFS). CAR-T cellular kinetics parameters (Cmax, AUC0-28d, persistence) were quantified via qPCR and correlated with clinical outcomes. Safety assessment covered cytokine release syndrome (CRS), immune effector cell-associated neurotoxicity syndrome (ICANS), and infections.ResultsAt day 28 post-infusion, the CR and MRD-CR rates were 98% and 96%, respectively. With a median follow-up of 68.7 months, the 5-year OS and LFS rates were 74.9% and 67.8%. Multivariate analysis identified prolonged B-cell aplasia (BCA) duration (HR = 0.969, p = 0.021) and female sex (HR = 0.235, p = 0.032) as independent protective factors for LFS. Cellular kinetics analysis showed effective in vivo expansion in 98% of patients, with a median Cmax of 30,860 copies/μg DNA and a median time-to-peak of 10.5 days. The MRD-CR group at day 28 exhibited significantly higher Cmax and AUC0-28d (p = 0.017; p = 0.029) and superior CAR-T persistence (p = 0.030) compared to the non-MRD-CR group. Pre-infusion tumor burden levels did not significantly impact CAR-T expansion or duration. BCA duration positively correlated with CAR-T persistence (r=0.570, p < 0.001), but CAR-T expansion parameters (Cmax and AUC0-28d) did not significantly influence BCA. Regarding safety, grade ≥3 CRS occurred in 16% of patients, and ICANS in 10%. Pre-infusion MRD ≥ 10-3 was an independent predictor of severe CRS.ConclusionCD19 CAR-T therapy demonstrates highly effective MRD clearance and provides long-term survival benefits with a manageable safety profile in pediatric B-ALL patients with MRD positivity or chemotherapy intolerance. Effective CAR-T expansion occurs even at low tumor burdens. These findings support the potential for advancing CAR-T therapy into earlier treatment lines, although its value requires further validation in prospective studies.